PHYTOCHEMICAL STUDIES AND ANTIOXIDANT PROPERTIES OF FOUR MEDICINAL PLANTS USED IN CAMEROON - Biapa, Prosper-Cabral N.; Agbor, Gabriel A.; Oben, Julius E.; Ngogang, Jeanne Y. (African Journal of Traditional, Complementary and Alternative Medicines, 2007)
Four plants (Amphimas pterocaroides, Harungana madagascariensis, Myrianthus arboreus, and Cussonia barteri) that are commonly used in Cameroon for the management or reversal of anaemia were screened for their phytochemical content and antioxidant potential. Four extracts (methanolic, hydro-ethanolic, aqueous, and hydrolysed) from each of the plants were prepared and analysed. Qualitative phytochemical tests were used to detect the presence of alkaloids, tannins, saponins, flavonoids, glycosides and phenols, while three quantitative methods; Folin, Ferric Reducing Antioxidant Power (FRAP) and diphenyl -1, 2-picryl hydrazyl (DPPH) were used to determine the antioxidant potential of these extracts. With the exception of the extracts of Cussonia barteri (negative for triterpenes and phenols) and the aqueous extract of Harungana madagascariensis (negative result for cardiac glycosides and glycosides), all other extracts contained the phytochemicals tested. The highest antioxidant activities were observed in the hydrolysed extracts of each plant, while the aqueous extract showed the least activity irrespective of the method used. The presence of active phytochemical substances with antioxidant activities may provide substantial basis for the use of these plants in ethnomedicine.